Sporting Activities as a tool for Social Re-Inclusion and Integration. The projects of: a) The Greek Homeless Football Team and b) The PanAfrican Football Tournament - Αρώνης, Γεώργιος (Πανεπιστήμιο Πελοποννήσου, 2011)
The Greek homeless football team and the Pan African football tournament have been designed, introduced and developed as a tool of Social inclusion and integration of different individuals and groups in Greece. With this research we examined, presented and analyzed the different sociological theories and definitions, as introduced and developed over the last decades, in order to approach and present the current and most widely accepted terminology for the sociological process of inclusion, exclusion and integration. From our research it was found that the sporting project of the Greek homeless football team clearly contributes to the re-socialization and re-inclusion of the participants and that the sporting project of the Pan African tournament, even though it does not contributes to the integration of the participants involved, it functions like a social event where the participants form new social networks and have the opportunity to participate more to the African Union. Also, the significant contribution of the African Union is unique since it functions like the receiving society through which the participants mostly seek to integrate to the Greek society.
Keywords: Soccer - Greece - Social aspects; Ποδόσφαιρο - Ελλάδα - Κοινωνικές απόψεις; Social Exclusion; Social inclusion; Social Integration; African football; Greek homeless football team; Κοινωνικός αποκλεισμός; Κοινωνική ένταξη; Κοινωνική ενσωμάτωση; Αφρικανικό ποδόσφαιρο; Ελληνική ποδοσφαιρική ομάδα αστέγων